2007
DOI: 10.1111/j.1365-2486.2007.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Emission of herbivore‐induced volatile terpenoids from two hybrid aspen (Populus tremula×tremuloides) clones under ambient and elevated ozone concentrations in the field

Abstract: Tropospheric ozone levels are continuously rising due to human activities in the 21st century. Although the phytotoxic impact of ozone on plants has been well documented, the effect of ozone on plant emissions has received little attention. We have conducted a field-based investigation utilizing two clones of hybrid aspen (Populus tremula L. Â P. tremuloides Michx.) in a free-air ozone concentration enrichment (FACE) facility. The effects of chronic exposure to moderately increased concentrations of ozone on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 56 publications
1
86
2
Order By: Relevance
“…Third, we used the conventional calculation methods for emission determination, although the underlying assumptions of these algorithms might be very different for the actual production pathways (Grote et al, 2013). Fourth, the cBVOC emissions of isoprene and monoterpene might change depending on temperature and light under stressed conditions (Behnke et al, 2009;Blande et al, 2007;Niinemets, 2010). Fifth, emission potentials of cBVOCs based on cut plants/branches may be somehow lower (e.g., max 1-5 %, Ghirardo et al, 2011) than those from uncut branches due to disturbance in carbon allo-cation (Funk et al, 1999).…”
Section: Uncertainties Of the Absolute Estimatesmentioning
confidence: 99%
“…Third, we used the conventional calculation methods for emission determination, although the underlying assumptions of these algorithms might be very different for the actual production pathways (Grote et al, 2013). Fourth, the cBVOC emissions of isoprene and monoterpene might change depending on temperature and light under stressed conditions (Behnke et al, 2009;Blande et al, 2007;Niinemets, 2010). Fifth, emission potentials of cBVOCs based on cut plants/branches may be somehow lower (e.g., max 1-5 %, Ghirardo et al, 2011) than those from uncut branches due to disturbance in carbon allo-cation (Funk et al, 1999).…”
Section: Uncertainties Of the Absolute Estimatesmentioning
confidence: 99%
“…These studies include both beetle infestation studies and fungal inoculation studies and have found significant increases in monoterpenes due to beetle attack (e.g. Gara et al, 1993;Litvak and Monson, 1998;Jost et al, 2008;Amin et al, 2012;Prieme et al, 2000;Blande et al, 2007;Brilli et al, 2009). Insect herbivory can induce both substantial increases in total monoterpene emissions from vegetation and changes in the emission profile, with implications for atmospheric composition.…”
Section: A R Berg Et Al: the Impact Of Bark Beetle Infestations Onmentioning
confidence: 99%
“…Current evidence suggests that several global change drivers such as ozone concentration can also affect both constitutive and herbivoreinduced BVOCs production (Loreto et al, 2007;Vuorinen et al, 2005;Blande et al, 2007). Ozone causes biochemical and physiological changes leading to the inhibition of photosynthesis and a consequent decrease in plant growth (Guderian et al, 1985), often associated with visible injuries (Loreto et al, 2001;Vollenweider and Gunthardt-Georg, 2005).…”
Section: E Bourtsoukidis Et Al: Ozone Stress As a Driving Force Of mentioning
confidence: 99%